Changes of macrominerals and calcitropic hormones in serum of periparturient dairy cows subject to subclinical hypocalcaemia. Issue 1 (February 2018) - Cai, Chuanjiang; Kong, Yezi; Wu, Dianjun; Wang, Jianguo
Abstract : The aims of the study reported in the Research Communication were to evaluate changes of macrominerals and major calcitropic hormone concentrations in 51 healthy dairy cows over the peripartum period, and to compare those cows with 51 cows subject to subclinical hypocalcaemia (SCH) on calving day. The results showed that serum calcium (Ca) and potassium (K) concentrations were lowest in the healthy periparturient dairy cows at parturition, while sodium (Na) and parathyroid hormone (PTH) concentrations were highest. Serum magnesium (Mg), chloride (Cl) and phosphorus (P) concentrations were highest 1 wk prepartum, however, the concentration of 1, 25-dihydroxyvitamin D3 [1, 25(OH)2 D3 ] was highest 1 wk postpartum. The dairy cows with subclinical hypocalcaemia (SCH) had significantly lower serum levels of Ca, K, Na, Mg, Cl, 1, 25(OH)2 D3 and glucose and had significantly higher levels of serum P, non-esterified fatty acids (NEFA) and β-hydroxybutyrate (BHBA) than their healthy counterparts on calving day. However, the serum calcitonin and PTH concentrations were not significantly different between the two groups. These data demonstrated that the concentrations of macrominerals and major calcium regulating hormones of cows change dramatically over the peripartum period. Furthermore, SCH was associated with a risk of the development of ketosis and fatty liver.